Fluidity between ethno-religious and national identifications: a study of identity and ethics in Mauritius - Ragoo, Ramesh (Department of Religious Studies, 2023)
Mauritius, an island with a population of nearly 1.3 million, is composed essentially of different local diasporas with numerous religious backgrounds. After more than three centuries of active cohabitation, a cosmopolitan and democratic nation is emerging. One of the traits of the island is the relatively peaceful co-existence of a diversity of religions and cultures, often considered a unique case of reference for the world. On the other hand, although the Mauritian constitution (1968) and public discourses by leaders of successive governments advocate for a democratic secular state, the nexus between communities (including religions as per the constitution) and political power predominates. At times, small tensions or communal conflicts do arise, which incite for research on sustainable peace. Other faiths have also emerged, cutting across traditional communities and breaking the tie with political power. Moreover, the legal requirement for legislative candidates at national elections to identify themselves with one of the four constitutional communities has become controversial. Against this background, this qualitative research, based on a social identity theory and employing an autoethnographic approach, aims to analyze the contributions of academics and religious organizations to the creation of a sustainable plural Mauritian society. A particular attention is paid to interfaith dialogue, with an emphasis on common religious values and ethics, which is gaining importance to address the 21st century social and national issues. Religion, and particularly the Council of Religions, constituted at the turn of this century, play a leading role in the transition from a multi-cultural, communally centered society to an intercultural and cosmopolitan one. To narrow down the study, two areas shall be examined: self-identification and ethics, from legacy to advocacy.